A Mixed Methods Evaluation of Adolescent Friendly Health Clinic Under National Adolescent Health Program, Puducherry, India - Thulasingam Mahalakshmy; Kariyarath Cheriyath Premarajan; Kathirvel Soundappan; Kanagarethinam Rajarethinam; Yuvaraj Krishnamoorthy; Adhisakthi Rajalatchumi; Vijayageetha Mathavaswami; Deepika Chandar; Palanivel Chinnakali; Amol R. Dongre (Indian J. Pediatr., 2019)
Objectives To assess the awareness and utilization of Adolescent Friendly Health Clinic (AFHC) services among school going adolescents (14-19 y) and to explore the forces 'for' and 'against' the utilization of AFHC services in Puducherry, India. Methods This mixed-methods study was conducted in two primary health centres. Record review assessed the utilization of AFHC service. Survey assessed the awareness on AFHC services and self-reported illnesses and their treatment seeking behavior. Group interviews were conducted with adolescent girls, boys and healthcare providers. A summative content analysis was done to organize the 'for' and 'against' forces for service utilization. Results Of the 311 adolescents, less than 50% were aware of the services available at AFHC. Utilization of Weekly Iron and Folic Acid Supplementation was good. Only 2-10% of adolescents consulted the outpatient services of the Primary Health Centre for the treatment of their health problems. The authors found low utilization of AFHC services (15% among girls, zero among boys). One of the reasons for low utilization was poor awareness. Though free sanitary napkins motivated the girls to avail the services, boys considered the AFHC as a girl's clinic. Healthcare providers suggested that building rapport and trust with adolescents and their parents, involving school teachers and ensuring privacy in the clinic would increase the utilization. Conclusions There is a huge gap between the awareness and utilization of AFHC services. The reasons for non-utilization were poor awareness and misconceptions about the clinic. Training of health staffs on communication skills, and supportive supervision could improve the utilization.
Keywords: Occupational Safety and Health Management System; Textile industry